Cancer Stem Cells – Are Surface Markers Alone Sufficient? - P. Nagare, Rohit; Sneha, Smarakan; Krishna Priya, Syama; S. Ganesan, Trivadi (Current Stem Cell Research & Therapy, 2017)
The identification of Cancer Stem Cells (CSCs) in leukemia has opened a new field in cancer research. This has led to the identification of similar cells in other types of cancer. CSCs express distinct surface markers and functional properties which distinguish them from the rest of the cells within a tumor. Due to variability in identification of CSCs in a particular type of cancer (except brain, breast and leukemia), surface markers alone may not be sufficient. It is critical to identify and isolate this small population of cells from the heterogeneous tumors to understand their pathogenesis. Identification of surface markers together with intrinsic properties of CSCs like colony formation, Hoechst exclusion or ALDEFLUOR assay may be useful in isolating more primitive and highly pure CSCs from a heterogeneous population of malignant cells. This review critically analyses various techniques and methods along with their advantages and disadvantages that are employed in identifying CSCs from different types of cancers.
Keywords: Cancer stem cells